PENGARUH LIKUIDITAS, UKURAN PERUSAHAAN, DAN STRUKTUR MODAL TERHADAP NILAI PERUSAHAAN PADA SEKTOR MANUFAKTUR YANG TERDAFTAR DI BEI TAHUN 2012-2014 - Zaenal Abidin, 12.05.52.0208; Poerwati, Rr. Tjahjaning (Students Journal of Accounting and Banking, 2016)
The study examined the effect of Liquidity, the size of the company and the capital structure on the value of companies. This research was conducted at the Indonesian Stock Exchange by using a go public manufacturing companies that have go public. The sampling method used purposive sampling with the observation period from 2012 to 2014. Relationship and (or) influence between variable is described by using multiple regression analysis. The results showed that the size of the company has positive effect and significant to the corporate value. Whereas the positive effect was not significant liquidity and capital structure significant negative effect on the company value. Keywords: Liquidity, Company Size, and Struktur of Capital and Corporate Value